Do Topics about Islam Better Facilitate English Writing Skills of Students in Islamic Colleges? Teachers’ and Students’ Reflections - Asmiyah, Siti; Safriyani, Rizka (Journal of English Teaching and Learning Issues, 2024)
Many studies have explored various strategies and approaches to facilitate students’ learning to write in English. However, few studies investigated the potential use of localized, familiar, and more personalized topics to develop students’ English writing skills. Considering Krashen’s comprehensible input hypothesis and Piaget’s constructivist approach, this study aimed to explore whether topics about Islam can better facilitate students' learning to write in English in Indonesian Islamic colleges. A mixed method design, qualitative method through interviews with seven English writing lecturers from four Islamic colleges in Indonesia, and quantitative method using a student survey, which was responded to by 100 students, became the source of data. The findings informed that a process-oriented approach, positive feedback, and freedom of and familiarity with topics were the main contributing factors to students' English writing development. The salient findings suggested that careful consideration of topic selection and vocabulary familiarity should be made when assigning writing tasks using topics about Islam in Islamic colleges.